Determinación de la calidad fisiológica de cinco genotipos de semillas de maíz (zea mays) en condiciones de campo y laboratorio. - Chicaiza Gómez, Dominica Alejandra (2022)
Maize (Zea mays L.) is one of the most important cereals in the world, in Ecuador it stands out as one of the main raw materials for agribusiness, it has wide genetic diversity, it adapts to the most diverse climatic conditions and it is used from the basic source of food, direct and indirect by human to the most demanding industrial technologies such as: cosmetics, food, and even biofuels. Its production depends completely on the production of worldwide seeds, a fact that has required large investments in the sector, aiming at the development of new cultivars and obtaining high quality seeds which benefit and generate income in all subsequent stages. Although there are developed methodologies along time and used routinely to assess seed quality, adaptations and adjustments are required each time according to the reality and objectives of the implemented studies. The objective of this research work was to evaluate the physiological quality of seeds of five tropical hard yellow maize genotypes, SOMMA 6215, 2B-604, INIAP H-554, INIAP H-551 and NB-7443, through conventional vigor tests: physical, physiological, biochemical, and resistance. 400 seeds were studied for each test, taken randomly from the work sample in four repetitions. With the use of conventional vigor tests, it was possible to detect efficiently the quality levels of the studied maize seed genotypes. This fact allows to conclude that all the used vigor tests, revealed efficiently various levels of physiological quality of seeds, highlighting the genotypes NB-7443, INIAP H – 554, and INIAP H - 551 in descending hierarchical order and the genotypes 2B 604 and SOMMA 6215, showed poor performance with negligible vigor and viability.